Reforming the Electric Power Industry in Developing Economies - Andrea Dertinger; Lion Hirth (ZBW – Leibniz Information Centre for Economics, 2019)
Since the 1990s, many developing countries have restructured their electric power industry. Policies such as break-ing up, commercializing and privatizing utilities, allowing for independent power producers, installing independent regulators, and introducing competitive wholesale markets were meant to improve the industry's efficiency and service quality. We exploit more than 30 years of data from over 100 countries to investigate the impact of power sector reforms on efficiency (represented by network losses) and access to electricity (represented by connection rates and residential power consumption). Crucially, reforms are likely to be endogenous with respect to sector performance: a crisis in electricity supply might well trigger reform efforts. We deal with endogeneity using reform activity in neighboring countries as an instrument. Our results suggest that reforms strongly and positively impact electricity access. According to our preferred specification, a full reform program would increase connection rates by 20 percentage points and per capita consumption by 62 percent: these are large effects that are stable across a range of robustness checks. Moreover, the effect of improving access is largest in South Asian countries. In con-trast to previous studies, we do not find robust evidence to support the theory that reforms reduce network losses.
Additional information: Please cite as: Dertinger, Andrea & Lion Hirth (2020): “Reforming the electric power industry in developing economies: Evidence on efficiency and electricity access outcomes”, Energy Policy 139, https://doi.org/10.1016/j.enpol.2020.111348.
Keywords: 330